23.8k views
1 vote
Solve for x.

6(x – 1) = 9(x + 2)

2 Answers

4 votes

Answer:

Simplify the left side.

6x−6=9(x+2)6x-6=9(x+2)

Simplify 9(x+2)9(x+2).

6x−6=9x+186x-6=9x+18

Move all terms containing xx to the left side of the equation.

−3x−6=18-3x-6=18

Move all terms not containing xx to the right side of the equation.

−3x=24-3x=24

Divide each term by −3-3 and simplify.

x=−8

User Aaron Queenan
by
5.8k points
4 votes

Answer:

The value of the equation for x is -8.

Explanation:

Consider the provided equation.


6(x-1)=9(x+2)

We need to solve the equation for x.

Distributive property:


a(b+c)=ab+ac

Use the above property to solve the provided equation.


6x-6=9x+18

Subtract 6x from both the sides.


6x-6-6x=9x-6x+18


-6=3x+18

Subtract 18 from both the sides.


-6-18=3x+18-18


-24=3x

Divide both the sides by 3.


x=-8

Hence, the value of the equation for x is -8.

User Joanna Mamczynska
by
5.9k points